2008
DOI: 10.1590/s1516-89132008000700017
|View full text |Cite
|
Sign up to set email alerts
|

Internal exposure in nuclear medicine: application of IAEA criteria to determine the need for internal monitoring

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
4
0
3
Order By: Relevance
“…Dantas et al . [ 23 ] observed that 131 I presents a high risk, and internal monitoring of 131 I should be included in the radiological protection plan, especially when used in therapeutic applications where the quantity of activity administered to each patient is usually several tens of millicuries. Bento et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dantas et al . [ 23 ] observed that 131 I presents a high risk, and internal monitoring of 131 I should be included in the radiological protection plan, especially when used in therapeutic applications where the quantity of activity administered to each patient is usually several tens of millicuries. Bento et al .…”
Section: Discussionmentioning
confidence: 99%
“…The second part is the study of the necessity of internal monitoring for nuclear medicine staff. Researchers in Chile [ 21 ], Portugal [ 22 ], Brazil [ 23 ] have carried out some research based on the aforementioned methodology to determine whether staff should be subjected to internal monitoring. Since the 1980s, there have been only a few studies and a small number of reports on the work of internal exposure in the field of nuclear medicine in China [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For thyroid diseases, 131 I is used for diagnostic and therapeutic purpose (3)(4)(5). When occupational workers process and labels the unsealed liquid sources with labeling compounds, the sources may enter their systems through inhalation and ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to short half life the internal radiation risk that it poses may sometimes be over looked. Although it is recognized that in nuclear medicine centers external exposure is usually higher than internal exposure, the risks associated with intakes should be estimated in each case and, if necessary, staff involved in the handling of unsealed sources should be routinely monitored in order to ensure that individual doses are kept as low as possible [1]. Internal monitoring should also be performed in response to an accident or suspected inhalation or ingestion intake.…”
mentioning
confidence: 99%